ANALISIS PENGARUH PROMOSI, KUALITAS DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO BUSANA LADYFAMESHOP BANDAR LAMPUNG - Armalia Reny (STIE Mahardhika, 2019)
Society needs to dress up and dress is very advanced and follows the world fashion trends, so that big people’s desire to follow the development and style of dress according to the fashion new trends. This study was conducted in search of how much influence arises from each variable that is promotion, quality, and price in the independent variable.In determining the number of samples to be taken, the researcher used a simple random sampling technique by taking samples at random regardless the strata found in the population. Because it is believed that the sample was homogenous. Determination of the number of samples of research carried out by using the computation slovin. Based on the calculation formula slovin, the study used sample as many as 71 customers Ladyfameshop clothing store located in Bandar Lampung. Based on partial analysis, it turns this study show that each of the independent variables examined in this particular study has convincing influence on the dependent variable. The variable is evident in the promotion,quality, and price have a convincing influence on the dependent variable is purchase decisions on Ladyfameshop Clothing Stores Bandar Lampung. Simultaneous testing, evidently the results prove that each of the independent variables (Promotion, Quality, and Price) simultaneously has significant influence on purchase as dependent variable of the store purchasing decisions Ladyfameshop Bandar Lampung.